Emerging applications, technologies, and services in wireless communications: 5G to 6G evolution - Servetnyk , Mykola; Servetnyk , Ruslan (Social Development and Security, 2021)
The fifth-generation (5G) of wireless communications was launched worldwide in 2020 with solid technical specifications and standards. Therefore, the focus of major vendors and academies is now switching towards deployment of beyond 5G (B5G) communications and 6G. As a result, provision and trends for global developments appear to outline requirements and services to satisfy future societal needs. This article provides a vision for the post-5G era of wireless communications, which serves as a research guide for scientists and commercial organizations. Current achievements of 5G New Radio (5G NR) are capable of bringing human-centric communications to their limit with applications such as Extended Reality (XR), Internet-of-Things (IoT), Smart Healthcare, 4K video streaming, etc. Therefore, we suggest that machine-centric communications will now emerge as a new part of 6G networks. To justify this perspective, we provide a systematic overview of emerging applications in wireless communications. We show how and why these services are possible by identifying key enabling technologies and advances in the manufacturing process. Further, we analyze trade-offs between solutions and required cost, which is essential for business model planning of 6G. Finally, issues behind the commercialization of future technologies, such as social and health factors, integration with existing networks, and inevitable performance limits from the basic sciences, are discussed.